A systematic review of isotretinoin dosing in acne vulgaris - Aoife U. Daly; Rui Baptista Gonçalves; Eva Lau; Joanne Bowers; Naayema Hussaini; Maria Charalambides; Jack Coumbe; Carsten Flohr; Alison M. Layton (Wiley, 2023)
Abstract How does low‐dose oral isotretinoin compare with recommended and high‐dose oral isotretinoin in terms of efficacy, adverse effect profile, duration of remission, economic profile and rate and severity of relapse? A systematic literature search of EMBASE, MEDLINE, PubMed and The Cochrane Library from 1983 to July 2022 was conducted to identify randomised control trials (RCTs), cohort studies and cross‐sectional studies investigating the treatment of acne vulgaris with oral isotretinoin. This systematic review of the literature sought to explore and compare the use of different isotretinoin dosing regimens. Primary outcomes were efficacy, relapse, and safety profiles of oral isotretinoin of varying doses. Secondary outcomes included adverse events and economic considerations. The quality of studies, including risk of bias was assessed using GRADE (Grading of Recommendations, Assessment, Development and Evaluations). A total of 32 studies were included. Severe acne responds better to conventional or high fixed daily doses of isotretinoin. In cases of mild to moderate acne, where oral isotretinoin was prescribed, clearance rates were comparable with low, conventional or high dosage regimens. Despite this, relapse was more frequent in those treated with a lower dose. The severity of mucocutaneous adverse effects worsens as the dose of isotretinoin is increased. Comparison between studies was challenging due to differing methods of assessment, outcome measures and duration of follow‐up. This review highlights the need for an adequately powered RCT comparing low, conventional and high doses of oral isotretinoin to establish optimal dosing for treatment and prevention of relapse in acne vulgaris.